Ultrastable plasmonic nanofluids in optimized direct absorption solar collectors. (1st November 2019) - Sharaf, Omar Z.; Rizk, Nahla; Joshi, Chakra P.; Abi Jaoudé, Maguy; Al-Khateeb, Ashraf N.; Kyritsis, Dimitrios C.; Abu-Nada, Eiyad; Martin, Matthew N.
Graphical abstract: Highlights: Ultrastable solar nanofluids with broadband photothermal absorption were prepared. A stabilization technique circumventing any need for free surfactants was developed. Colloidal stability was maintained for 16 months, a new record for solar nanofluids. Long-term storage, incremental heating, and increased loading tests were conducted. Nanofluid-specific design vectors were optimized for efficient solar conversion. Abstract: Nanofluids used in low-flux direct absorption solar collectors (DASCs) typically encounter critical stability issues due to long-term storage, elevated temperatures, high particle concentrations, and fouling from free surfactants. Here, we developed ultrastable nanofluids, and their properties were used to computationally optimize DASC designs. Broadband photothermal absorption was achieved using citrate- (CIT-) and polyethylene glycol-coated (PEG-) gold nanoparticles, circumventing the need for free surfactants. The nanofluids were subjected to long-term ambient storage, high particle concentrations, and incremental heating to analyze their stability and utility in DASCs. Electrosteric stabilization (PEG + CIT) provided superior colloidal stability and more consistent optical properties; chemical and colloidal stability was verified for 16 months, the longest demonstration of stable nanofluids under ambient storage in the solar literature. Optical measurements of the stabilized solar nanofluids were fed into a DASC optimization model. A constrained generalized pattern search (GPS) algorithm simultaneously maximized collector thermal power-gain and minimized nanoparticle mass loading, while maintaining a collector temperature-gain target. Ultimately, by simultaneously developing ultrastable solar nanofluids, minimizing nanoparticle loading requirements, and maximizing collector thermal power gain, the outcomes from this study are considered significant steps towards deploying efficient and reliable low-flux, nanofluid-based DASCs in field applications.